2015
DOI: 10.17219/acem/40454
|View full text |Cite
|
Sign up to set email alerts
|

Gene Polymorphisms of Tumor Necrosis Factor Alpha and Antioxidant Enzymes in Bronchial Asthma

Abstract: Background. Bronchial asthma is an inflammatory disease resulting from a combination of genetic and environmental factors. Single nucleotide polymorphisms in the regulatory regions of cytokine and antioxidant enzyme genes may affect cytokine production and enzyme activity, and thus play a contributory role in asthma pathogenesis. Objectives. The aim of this study was to examine the association of manganese superoxide dismutase (MnSOD) Ala16Val, catalase (CAT) A-21T and tumor necrosis factor alpha (TNF-α) G-308… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…TNF-α is a proinflammatory cytokine that is mainly secreted by multinuclear giant cells, with a wide range of biological activities, including the regulation of host immune functions and the inflammatory reaction process [24]. that TNF-α participates in several key processes of tumor progression, including oncogene activation, DNA damage, and tumor metastasis [25].…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a proinflammatory cytokine that is mainly secreted by multinuclear giant cells, with a wide range of biological activities, including the regulation of host immune functions and the inflammatory reaction process [24]. that TNF-α participates in several key processes of tumor progression, including oncogene activation, DNA damage, and tumor metastasis [25].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IL-10 can suppress macrophage activity by inhibiting the production of interferon gamma, IL-2, IL-12, and IL-18 and that the modulation of the inflammatory response is essential to preserve immune system balance [ 15 ]. Tumor necrosis factor α (TNF-α) is a multifunctional and pro-inflammatory cytokine that can respond to inflammation, infection, and injury by mast cells, macrophages, eosinophils, epithelial cells, and neutrophils in asthma pathogenesis [ 16 ]. However, few studies have systematically investigated the inflammatory cytokine levels in patients with asthma, AECOPD, and ACOS.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggest that naringenin could markedly decrease the release of IL-8 and TNF-α, protecting cells from CSE-induced inflammatory reaction. IL-8 and TNF-α are essential inflammatory cytokines of pulmonary illnesses [ 52 , 53 ]. Clinical studies have demonstrated the correlation between pulmonary illnesses and the content of IL-8 and TNF-α [ 54 ], and strong correlations have been found between the number of sputum cells (macrophages and neutrophils) and proinflammatory cytokine levels (IL-8 and TNF-α) [ 55 ], suggesting that IL-8 and TNF-α are suitable for evaluating the inflammatory reaction in BEAS-2B cells.…”
Section: Discussionmentioning
confidence: 99%